Communicative approach: teaching and learning Arabic for non-native speakers - Eltingari, Salih Mahgoub Mohamed; Hassan, Fekri Abidin (Chronopub Publications, 2018)
This research through an inductive descriptive approach, aims to encourage teachers of Arabic as second language to apply the communicative approach in their teaching. The two main research questions to be answered by this research are:1)What is communicative approach? 2) How feasible it is to be applied in the teaching of Arabic as second language? The research first describes the principles of the approach. It then discusses its suitability in the teaching of Arabic as it provides multiple benefits. The main benefit is it allows communication in the target language through its fun and exciting activities. It also enables ‘harmony’ to be created between students and teachers as well as taking into account the psychological and social aspects of the students especially in terms of error correction.